The transmigration of Timothy Archer - Dick, Philip K. (Vintage Books, 1991)
Bishop Timothy Archer, formerly a lawyer, searches for God by means of mysticism, seances, and a quest for the source of records--written earlier than the Bible--of Christ's life on earth.